2018
DOI: 10.1123/ijsnem.2017-0161
|View full text |Cite
|
Sign up to set email alerts
|

Adding Fish Oil to Whey Protein, Leucine, and Carbohydrate Over a Six-Week Supplementation Period Attenuates Muscle Soreness Following Eccentric Exercise in Competitive Soccer Players

Abstract: Soccer players often experience eccentric exercise-induced muscle damage given the physical demands of soccer match-play. Since long chain n-3 polyunsaturated fatty acids (n-3PUFA) enhance muscle sensitivity to protein supplementation, dietary supplementation with a combination of fish oil-derived n-3PUFA, protein and carbohydrate may promote exercise recovery. This study examined the influence of adding n-3PUFA to a whey protein, leucine and carbohydrate containing beverage over a 6 week supplementation perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
4
25
3
Order By: Relevance
“…While previous research has indicated FO supplementation may attenuate losses in muscular strength following vigorous exercise [35,54,55], our results do not support these findings, which is similar to the majority of research to date [34,40,41,53,55]. It is thought that FO may reduce the amount of damage assumed by the worked skeletal muscle and conserve strength and power production, and thus muscular performance.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…While previous research has indicated FO supplementation may attenuate losses in muscular strength following vigorous exercise [35,54,55], our results do not support these findings, which is similar to the majority of research to date [34,40,41,53,55]. It is thought that FO may reduce the amount of damage assumed by the worked skeletal muscle and conserve strength and power production, and thus muscular performance.…”
Section: Discussioncontrasting
confidence: 92%
“…The literature to date has been published examining FO supplementation and perceived soreness following damaging or vigorous exercise [32][33][34]38,41,[53][54][55][56]. While a direct comparison is impossible due to the array of damaging or vigorous exercise protocols that have been studied (e.g., eccentric squat, bench stepping, eccentric exercise of the elbow flexors), our finding that 6G FO supplementation reduces perceived soreness following a single bout of damaging exercise has been demonstrated in previous research.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…week period prior to performing an intense exercise bout (Philpott et al, 2018). In the 72 hours following the muscle damaging exercise, the soccer players in the n-3PUFA plus protein group reported reduced levels of muscle soreness.…”
Section: Team-based Athletesmentioning
confidence: 99%
“…A recent study in 30 male athletes found that 6 weeks of supplementation with 0.55 g EPA and 0.55 g DHA reduced muscle soreness after eccentric exercise, without an effect on muscle function [54]. Reduced soreness in amateurs due to supplementation with EPA/DHA has been consistently reported [34,40,46].…”
Section: The Influence Of Dose and Study Duration In Athletes And Amamentioning
confidence: 99%